Sílica mesoporosa como suporte sólido para o ancoramento da molécula 4-amino-3-hidrazino-5-mercapto-1,2,4-triazole e aplicação na adsorção de Cu(II), Cd(II), Ni(II), Pb(II) e Co(II) em amostras aquosas - Ivassechen, Janaíne do Rocio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The direct determination of metals present at trace levels in natural water samples is generally difficult due to the presence of interfering species. Metals that were studied, Cu(II), Pb(II), Co(II), Ni(II) and Cd(II) are of environmental interest because of its intensive use, distribution, and as a consequence of its non-degradability can be accumulated in environmental matrices manifesting toxicity. In this project was developed a mesoporous silica as solid support for the anchoring of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole molecule to be applied in the adsorption/removal of metals from aqueous solution. The material was characterized by infrared spectroscopy (FTIR), which showed bands at 1649 and 1690- 790 cm-1, characteristic of NH bonds of primary amines, existing in molecule ligand. The nuclear magnetic resonance 13C and 29Si (NMR) confirm the anchoring of the ligand. Measurements of specific surface area by the BET method and pore diameter resulted in an area of 795.51 ± 1.14 m2 g-1 and pores in a range from 1.1 to 7.1 nm. Scanning Electron Microscopy (SEM) showed that the material has spherical shape with sizes of approximately 10 μm and the analysis by Energy Dispersive X-ray (EDX) showed a homogeneous distribution of silylant over material surface. Thus, it was confirmed the occurrence of the modification reaction. The material was applied in adsorption studies to determine its maximum adsorption capacity, as well as studies of the influence of pH and kinetic studies on the balance process. The experiments were performed by the batch method. The first test was the pHPZC which indicates the best pH range (5-9) for the adsorption. Adsorption studies showed the best results when pH was near 6 and the adsorption equilibrium was attained after 50 minutes of stirring time. For all species investigated the adsorption process is better described by the pseudo- second order kinetic model. With these parameters established the maximum adsorption capacity values found were 0.129, 0.102, 0.105, 0.113 and 0.076 mmol g-1 for Cu(II), Ni(II), Pb(II), Co(II) and Cd(II), respectively. Modified silica was also applied in the preconcentration of Cu(II) from aqueous samples with 20 fold enrichment factor and the packed column proved to be stable over 24 cycles of adsorption/desorption.

A determinação direta de metais presentes em baixas concentrações em amostras de águas naturais é geralmente dificultada devido à presença de espécies interferentes. Os metais que foram estudados, Cu (II), Pb(II), Co (II), Ni (II) e Cd (II) são de interesse ambiental em razão de seu uso intensivo, distribuição e por serem absolutamente não-degradáveis podem acumular-se em matrizes ambientais manifestando toxicidade. Neste projeto desenvolveu-se a sílica como suporte sólido para o ancoramento da molécula 4-amino-3-hidrazino-5-mercapto-1,2,4-triazole e sua aplicação na adsorção/remoção de íons em solução aquosa. O material foi caracterizado por espectroscopia na região do infravermelho (FTIR), o qual apresentou bandas em 1690- 1649 e 790 cm-1 , característica de ligações N-H de aminas primárias do ligante. A ressonância magnética nuclear de 13C e 29Si (RMN) comprovam o ancoramento do ligante. As medidas de área de superfície específica pelo método de BET e diâmetro de poro resultaram em uma área de 795,51 ± 1,14 m2 g-1 e poros numa gama de 1,1 a 7,1 nm. A Microscopia Eletrônica de Varredura (MEV) mostrou que o material tem formato esférico com tamanhos aproximadamente de 10 μm e a Análise por Energia Dispersiva de Raios X (EDX) mostrou uma distribuição homogênea do sililante por toda a superfície do material. Com isso, confirmou-se a ocorrência da reação de modificação. O material foi aplicado em estudos de adsorção para determinação da sua capacidade máxima, bem como estudos da influência do pH e estudos cinéticos no processo de equilíbrio Os experimentos foram realizados pelo método de batelada. O primeiro teste foi o pHPZC, que indica a melhor faixa de pH (5-9) para a adsorção. Os estudos de adsorção dos metais em solução apresentaram o melhor resultado quando o pH era igual a 6, o equilíbrio de adsorção foi atingido depois de 50 minutos de agitação. Para todas as espécies investigadas o processo de adsorção é melhor descrito pelo modelo de pseudo- segunda ordem. Com esses parâmetros estabelecidos os valores de capacidade máxima de adsorção foram encontrados, sendo 0,129; 0,102; 0,105; 0,113; e 0,076 mmol g-1 para o Cu, Ni, Pb, Co e Cd, respectivamente. A sílica modificada foi aplicada na pré-concentração de Cu (II) em amostras aquosas. Com um fator de enriquecimento de 20 vezes, a coluna provou ser estável ao longo de 24 ciclos de adsorção/dessorção.
Mesoporous silica as the solid support for the anchoring of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole molecule and application in the adsorption of Cu (II), Cd (II), Ni (II), Pb (II) and Co (II) in aqueous samples
Keywords: Sílica gel; Adsorção; Espectroscopia de absorção atômica; Ressonância magnética nuclear; Íons metálicos; 4-amino-3-hidrazino-5-mercapto-1,2,4- triazole